The Relationship between the Length of Time Suffering from Cancer and the Quality of Life of the Family Caregiver of Cancer Patients in the Oncology Room - Anastasia Diah Larasati; Apolonia Antonilda Ina (Indonesian Journal of Global Health Research, 2024)
The number of cancers increases every year, with the chemotherapy treatment that must be undergone, the stage of cancer and the length of time the patient must undergo cancer can affect the quality of life of the accompanying family. The aim of this research is to look at the length of time suffering from cancer and the quality of life of the family accompanying cancer patients. This research is a quantitative descriptive study with a consecutive sampling technique of 40 respondents. Data was taken in the oncology inpatient room at RSD X in Semarang City. This research has passed the Ethical Clearance test from the local hospital. Data was collected using the WHO QOL BREF questionnaire and patient identity sheet. Data were analyzed using the Fisher test statistical test. The number of families who have a moderate quality of life with a family member who has had cancer for ≤ 2 years is 22 (55%). The results of the p value show that there is no relationship between the length of time a patient suffers from cancer and the quality of life of the family accompanying the cancer patient in the oncology room with the psychological and social domains being the most disturbed of the other four domains.